Changes in weight and body composition in physically active first year university students - Changmo Cho; Cruz, Angelita Bautista (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Previous studies showed that transition to university may pose a risk of weight gain among first year university students. However, researchers have overlooked to examine students with unique characteristics that might vary their susceptibility to weight gain. Aim of Study. The purpose of this study was to examine changes in body weight and body composition among physically-oriented first-year students. Material and Methods. A total of 86 physically active first year students participated in the study. Students’ body weight and other body composition variables were measured at three time points during their first year in university. Results. Overall, while no significant weight gain was found in first year students at the end of the study compared to the baseline, their average weight gain was lower than earlier findings. However, significant changes in % body fat of students were observed during their freshman year. Both male and female students experienced transitory changes in weight, fat mass, % body fat, and % skeletal mass during the study. Among the total cohort of students, more than 50% gained weight after 7 months in their freshman year despite their high level of physical activity participation. Conclusions. This study extends the literature concerning weight gain during transition from school to university among first year students and its association with physical activity. It also shows the potential role of culture affecting the incidence of weight gain in freshman students. Finally, the finding highlights the importance of weight gain prevention programs for firstyear university students, even if they are physically active.
Keywords: physical activity; weight gain; South Korea; physically-oriented students; Freshman 15